Adjuvant nivolumab versus ipilimumab (CheckMate 238 trial): Reassessment of 4-year efficacy outcomes in patients with stage III melanoma per AJCC-8 staging criteria. (September 2022) - Larkin, James; Weber, Jeffrey; Del Vecchio, Michele; Gogas, Helen; Arance, Ana M.; Dalle, Stephane; Cowey, C. Lance; Schenker, Michael; Grob, Jean-Jacques; Chiarion-Sileni, Vanna; Márquez-Rodas, Iván; Butler, Marcus O.; et al.
Abstract: Purpose: Nivolumab was approved as adjuvant therapy for melanoma based on data from CheckMate 238, which enrolled patients per American Joint Committee on Cancer version 7 (AJCC-7) criteria. Here, we analyse long-term outcomes per AJCC-8 staging criteria compared with AJCC-7 results to inform clinical decisions for patients diagnosed per AJCC-8. Patients and methods: In a double-blind, phase 3 trial (NCT02388906), patients aged ≥15 years with resected, histologically confirmed AJCC-7 stage IIIB, IIIC, or IV melanoma were randomised to receive nivolumab 3 mg/kg every 2 weeks or ipilimumab 10 mg/kg every 3 weeks for 4 doses and then every 12 weeks, both intravenously ≤1 year. Recurrence-free survival (RFS) and distant metastasis-free survival (DMFS) were assessed in patients with stage III disease, per AJCC-7 and AJCC-8. Results: Per AJCC-7 staging, 42.4% and 57.3% of patients were in substage IIIB and IIIC, respectively; per AJCC-8, 1.1%, 30.4%, 62.8%, and 5.0% were in IIIA, IIIB, IIIC, and IIID. After 4 years' minimum follow-up, the AJCC-7 superior efficacy of nivolumab over ipilimumab in patients with resected stage III melanoma was preserved per AJCC-8 analysis. No statistically significant difference in RFS between stage III substage hazard ratios was observed per AJCC-7 or -8 staging criteria (interaction test: AJCC-7, P  = 0.8115; AJCC-8, P  = 0.1051; P  = 0.8392 ((AJCC-7) and P  = 0.8678 (AJCC-8) for DMFS). Conclusions: CheckMate 238 4-year RFS and DMFS outcomes are consistent per AJCC-7 and AJCC-8 staging criteria. Outcome benefits can therefore be translated for patients diagnosed per AJCC-8. Highlights: Nivolumab superior to ipilimumab per American Joint Committee on Cancer version 7 (AJCC-7) was preserved when analysed per AJCC-8. Longer recurrence-free survival and distant metastasis-free survival with nivolumab across staging criteria and substages. Adjuvant nivolumab benefit and risk information for patients diagnosed per AJCC-8.